2017
DOI: 10.1097/pcc.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Career Development Support in Pediatric Critical Care Medicine: A National Survey of Fellows and Junior Faculty*

Abstract: Objective To determine the perceptions of current pediatric critical care medicine (PCCM) fellows and junior faculty regarding the extent and quality of career development support received during fellowship training. Design Web-based cross-sectional survey open from September to November 2015. Setting Accreditation Council for Graduate Medical Education (ACGME)-accredited PCCM fellowship programs. Participants PCCM fellows (2nd year or higher) and junior faculty (within 5 years of completing a PCCM fello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Providing a roadmap in the research career will attract them and alleviate worries for their future job security. A survey conducted in the United States reported that most clinical trainees felt that spending time and research activity efforts would not necessarily lead to their job security or even a better job ( 28 , 29 ). It should be necessary to build a program to nurture new researchers in Asia across countries and societies.…”
Section: Discussionmentioning
confidence: 99%
“…Providing a roadmap in the research career will attract them and alleviate worries for their future job security. A survey conducted in the United States reported that most clinical trainees felt that spending time and research activity efforts would not necessarily lead to their job security or even a better job ( 28 , 29 ). It should be necessary to build a program to nurture new researchers in Asia across countries and societies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most PCCM trainees aspire to practice in large academic institutions after completing PCCM fellowship training. 3 Our results indicate that only 74 (37.2%) of advertised available opportunities to newly graduated fellows were offered in academic centers. Cifra et al, in a survey of PCCM fellows, indicated that 11% of surveyed trainees planned to practice in nonacademic community-based hospital settings, and only 43% of surveyed PCCM fellows thought they have a good chance of obtaining their ideal PCCM opportunity.…”
Section: Discussionmentioning
confidence: 69%
“…They noted that the most common perceived barrier was the increased competition for limited job opportunities. 3 These job market imbalances could potentially impact job satisfaction among newly graduated PCCM physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for reduced publication productivity after completion of fellowship can be multifactorial, ranging from lack of time, funding, facilities, mentorship, to certainty of succeeding in academic positions. 21 While there is an ABP requirement for trainees to engage in scholarly activity during their fellowship, approximately 60% of these efforts do not culminate in a successful publication. 22 Our metrics of academic productivity using publication outcomes do also not account for time spent with higher clinical workloads, quality improvement initiatives, medical education, administration, or other roles that are necessary to the function of a PICU.…”
Section: Resultsmentioning
confidence: 99%